The significant impact of home pocket garden on the quality of life during the pandemic era - Sanusi, Aliyah Nur Zafirah; Abdullah, Fadzidah; Azmin, Aida Kesuma; Yusof, Zeenat Begam; Asif, Nayeem; Othman, Rosniza (2021)
Before the pandemic, residents in the Klang Valley tend to prioritize indoor living space to outdoor. This study analyzed the importance of outdoor green space in residential buildings. It consists of two objectives; to identify the type of home pocket gardens used and to evaluate the significant impact of home pocket gardens on the quality of life (QOL) during the pandemic. A survey was conducted using a five-point Likert scale and distributed to three housing communities within the Klang Valley. In conclusion, home pocket gardens provide a positive impact on the QOL during the pandemic.